Social Dynamics and Intellectual Traditions During the Umayyad Dynasty - Fatmawati, Fatmawati (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This article aims to analyze the social and intellectual aspects of the reign of the Umayyad Dynasty which was based in Damascus. The Umayyad dynasty was famous for its achievements in conquering territories and spreading the Islamic religion from Asia, North Africa to Europe. These brilliant achievements had an impact on changes in social structures and the strengthening of intellectual traditions. There are two focuses of study in this article, namely changes in the social structure of society and progress in the field of science. The research method used is a library research approach history, namely analysis of texts and information related to the study of the Umayyad Dynasty from various sources, then data analysis including data reduction (data reduction), display data and a picture of the conclusion or verification (conclusion drawing/verification) which is then concluded. The findings of this research are that there were changes in the social structure of society during the Umayyad Dynasty, especially with regard to non-Arab Muslims or conquered communities. Non-Arab people did not have the right to hold office during the Umayyad Dynasty, but they were more involved in intellectual traditions and created the initial foundations of knowledge in Islamic history. Artikel ini bertujuan untuk menganalisis sosial kemasyarakatan dan intelektual pada masa pemerintahan Dinasti Bani Umayyah yang berpusat di Damaskus. Dinasti Bani Umayyah terkenal dengan prestasinya dalam penaklukan wilayah dan menyebarkan agama Islam dari Asia, Afrika Utara sampai ke Eropa, prestasi yang gemilang tersebut berdampak kepada perubahan struktur sosial dan penguatan dalam tradisi intelektual. Ada dua fokus kajian dari artikel ini yaitu perubahan struktur sosial masyarakat dan kemajuan dalam bidang ilmu pengetahuan. Metode penelitian yang digunakan adalah penelitian kepustakaan dengan pendekatan sejarah yaitu analisis teks dan informasi yang terkait dengan kajian tentang Dinasti Bani Umayyah dari berbagai sumber, kemudian dilakukan analisis data meliputi reduksi data (data reduction), display data dan gambaran konklusi atau verifikasi (conclusion drawing/verification) yang kemudian disimpulkan. Temuan dari penelitian ini adalah terdapat perubahan struktur sosial kemasyarakatan pada masa Dinansti Bani Umayyah terutama berkaitan dengan orang-orang Islam nonArab atau masyarakat yang ditaklukkan. Orang-orang nonArab tidak memperoleh hak untuk bisa menjabat pada masa Dinasti Bani Umayyah, namun mereka lebih banyak berkecipung dalam tradisi intelektual dan menciptakan pondasi awal dalam ilmu pengetahuan dalam sejarah Islam.